Cover Picture: Silver‐Catalyzed Cascade Radical Cyclization for Stereoselective Synthesis of Exocyclic Phosphine Oxides (Chin. J. Chem. 3/2017). Issue 3 (March 2017) - Mao, Liuliang; Li, Yonghong; Yang, Shangdong
Abstract : The cover picture shows a concise and effective protocol for the synthesis of valuable exocyclic phosphine oxides via the process of free radical cascade cyclization. Waterwheel in series shows the implied meaning in the process of phosphorylation/ cascade cyclization of various 1, 6‐dienes involving the C—P and C—C bonds formation. More details are discussed in the article by Yang et al . on page 316–322. Abstract : The cover picture shows a concise and effective protocol for the synthesis of valuable exocyclic phosphine oxides via the process of free radical cascade cyclization. Waterwheel in series shows the implied meaning in the process of phosphorylation/ cascade cyclization of various 1, 6‐dienes involving the C—P and C—C bonds formation. More details are discussed in the article by Yang et al . on page 316–322.